Burden of Cardiovascular Disease among Multi-Racial and Ethnic Populations in the United States: an Update from the National Health Interview Surveys - Liu, Longjian; Núṅez, Ana E.; An, Yuan; Liu, Hui; Chen, Ming; Ma, Jixiang; Chou, Edgar Y.; Chen, Zhengming; Eisen, Howard J. (Frontiers in Cardiovascular Medicine, 2014)
Purpose: The study aimed to provide new evidence of health disparities in cardiovascular disease (CVD) and diabetes mellitus (DM), and to examine their associations with lifestyle-related risk factors across the U.S. multi-racial and ethnic groups. Methods: The analysis included a randomized population sample of 68,321 subjects aged ≥18 years old who participated in the U.S. 2012 and 2013 National Health Interview Surveys. Hypertension, coronary heart disease (CHD), stroke and DM were classified according to participants’ self-report of physician diagnosis. Assessments of risk factors were measured using standard survey instruments. Associations of risk factors with hypertension, CHD, stroke and DM were analyzed using univariable and multivariable analysis methods. Results: Non-Hispanic (NH)-Blacks had significantly higher odds of hypertension, stroke and DM, while NH-Asians and Hispanics had significantly lower odds of stroke and higher odds of stroke and higher odds of DM than NH-Whites (p<0.001). NH-Whites had higher odds of CHD than NH-Black, NH-Asians and Hispanics (p<0.001). Increased body weight, cigarette smoking and physical inactivity were significantly associated with increased odds of hypertension, CHD, stroke and DM (p<0.001). However, the strengths of associations between lifestyle-related factors and the study outcomes were different across racial and ethnic groups. NH-Asians with BMI ≥30 kg/m2 had the highest odds ratios (OR, 95%CI) for hypertension (5.37, 4.01-7.18), CHD (2.93, 1.90-4.52) and stroke (2.23, 1.08-4.61), and had the second highest odd ratios for DM (3.78, 2.68-5.35) than NH-Whites, NH-Blacks and Hispanics. Conclusion: CVD and DM disproportionately affect the U.S. multi-racial and ethnic population. Although lifestyle-related risk factors are significantly associated with increased odds of CVD and DM, the impacts of risk factors on the study outcomes are different by race and ethnicity.